Genetic polymorphism of toll-like receptors 4 gene by polymerase chain reaction-restriction fragment length polymorphisms, polymerase chain reaction-single-strand conformational polymorphism to correlate with mastitic cows - Gupta, Pooja H.; Patel, Nirmal A.; Rank, D. N.; Joshi, C. G. (Veterinary World, 2015)
An attempt has been made to study the toll-like receptors 4 (TLR4) gene polymorphism from cattle DNA to correlate with mastitis cows. In present investigation, two fragments of TLR4 gene named T4CRBR1 and T4CRBR2 of a 316 bp and 382 bp were amplified by polymerase chain reaction (PCR), respectively from Kankrej (22) and Triple cross (24) cattle. The genetic polymorphisms in the two populations were detected by a single-strand conformational polymorphism in the first locus and by digesting the fragments with restriction endonuclease Alu I in the second one. Results showed that both alleles (A and B) of two loci were found in all the two populations and the value of polymorphism information content indicated that these were highly polymorphic. Statistical results of χ(2) test indicated that two polymorphism sites in the two populations fit with Hardy-Weinberg equilibrium (p<0.05). Meanwhile, the effect of polymorphism of TLR4 gene on the somatic cell score (SCS) indicated the cattle with allele a in T4CRBR1 showed lower SCS than that of allele B (p<0.05). Thus, the allele A might play an important role in mastitis resistance in cows. The relationship between the bovine mastitis trait and the polymorphism of TLR4 gene indicated that the bovine TLR4 gene may play an important role in mastitis resistance.